E3 Ubiquitin Ligase-Mediated Regulation of Osteoblast Differentiation and Bone Formation - Shen, Jianlin; Fu, Bowen; Li, Yanfang; Wu, Yanjiao; Sang, Hongxun; Zhang, Heshi; Lin, Haibin; Liu, Huan; Huang, Wenhua (Frontiers in Cell and Developmental Biology, 2021)
The ubiquitin-proteasome system (UPS) is an essential pathway that regulates the homeostasis and function of intracellular proteins and is a crucial protein-degradation system in osteoblast differentiation and bone formation. Abnormal regulation of ubiquitination leads to osteoblast differentiation disorders, interfering with bone formation and ultimately leading to osteoporosis. E3 ubiquitin ligases (E3) promote addition of a ubiquitin moiety to substrate proteins, specifically recognizing the substrate and modulating tyrosine kinase receptors, signaling proteins and transcription factors involved in the regulation of osteoblast proliferation, differentiation, survival and bone formation. In this review, we summarize current progress in the understanding of the function and regulatory effects of E3 ligases on the transcription factors and signaling pathways that regulate osteoblast differentiation and bone formation. A deep understanding of E3 ligase-mediated regulation of osteoblast differentiation provides a scientific rationale for the discovery and development of novel E3-targeting therapeutic strategies for osteoporosis.